Lenin Reloaded Toward a Politics of Truth, sic 7 - Budgen, Sebastian; Kouvelakis, Stathis; Zizek, Slavoj (Duke University Press, 2007)
Lenin Reloaded is a rallying call by some of the world's leading Marxist intellectuals for renewed attention to the significance of Vladimir Lenin. The volume's editors explain that it was Lenin who made Karl Marx's thought explicitly political, who extended it beyond the confines of Europe, who put it into practice. They contend that a focus on Lenin is urgently needed now, when global capitalism appears to be the only game in town, the liberal-democratic system seems to have been settled on as the optimal political organization of society, and it has become easier to imagine the end of the world than a modest change in the mode of production. Lenin retooled Marx's thought for specific historical conditions in 1914, and Lenin Reloaded urges a reinvention of the revolutionary project for the present. Such a project would be Leninist in its commitment to action based on truth and its acceptance of the consequences that follow from action.